Sustainable Transport Strategies: A Case Study of Riyad, Saudi Arabia - Al Zohbi Gaydaa (E3S Web of Conferences, 2021)
Transport is considered as an important action zone for achieving sustainable development since it takes a significant part in the economy sector with its existence among the production pattern, at geographic ladder [1]. Although, it is evident that the transport sector is responsible for many environmental issues. Riyad city is suffered from severe pollution caused by extensive use of motorized transport. Thus, implementation of appropriate policy tools relieve the harmful effect of transport activities by attaining sustainable transport. This paper pursues to evaluate the sustainability situation of transportation sector in Riyad city by using real data. The current paper ended with some recommendations to achieve sustainable transportation in KSA. Results indicated that the increase of car ownership and travel demand, the low use of public transport, and the rise of air and noise pollution level and the high level of road mortality lead to make the transportation system of Riyad unsustainable. On the other hand, the Saudi government have already started to execute many planned projects to achieve sustainable transportation such as the metro and bus network in Riyad and the installation of charger station of electric vehicle. In addition, the Saudi government set out many policies and target such as Target 11.2 that aims to achieve sustainable transportation in KSA and Target 3.6 that intents to minimize the high mortality rate from road accidents.